Handbook of research on the strategic management of family businesses - Palma-Ruiz, Jesus Manuel, 1978-; Barros-Contreras, Ismael, 1968-; Gnan, Luca (Advances in business strategy and competitive advantage., 2020)
""This book examines the challenges and opportunities for the strategic management of family businesses"--Provided by publisher"--